First "in situ" determination of gas transport coefficients ( DO2, DAr, and DN2) from bulk gas concentration measurements (O2, N2, Ar) in natural sea ice. Issue 10 (7th October 2014) - Crabeck, Odile; Delille, B.; Rysgaard, S.; Thomas, D. N.; Geilfus, N.‐X.; Else, B.; Tison, J.‐L.
Abstract We report bulk gas concentrations of O2, N2, and Ar, as well as their transport coefficients, in natural landfast subarctic sea ice in southwest Greenland. The observed bulk ice gas composition was 27.5% O2, 71.4% N2, and 1.09% Ar. Most previous studies suggest that convective transport is the main driver of gas displacement in sea ice and have neglected diffusion processes. According to our data, brines were stratified within the ice, so that no convective transport could occur within the brine system. Therefore, diffusive transport was the main driver of gas migration. By analyzing the temporal evolution of an internal gas peak within the ice, we deduced the bulk gas transport coefficients for oxygen (DO2), argon (DAr), and nitrogen (DN2). The values fit to the few existing estimates from experimental work, and are close to the diffusivity values in water (10−5 cm2 s−1). We suggest that gas bubbles escaping from the brine to the atmosphere—as the ice gets more permeable during melt—could be responsible for the previously reported high transport coefficients. These results underline that when there is no convective transport within the sea ice, the transport of gas by diffusion through the brines, either in the liquid or gaseous phases, is a major factor in controlling the ocean‐atmosphere exchange.